Ficus capensis Thumb. (Moraceae): Review of Its Ethnomedicinal Uses, Pharmacological Activities and Phytochemical Constituents - , Kevwe Benefit Esievo; , Samuel Onuche Anthony; , Omolola Temitope Fatokun; , Oluyemisi Folashade Kunle (Archives of Current Research International, 2018)
Ficus capensis Thumb (Moraceae) also known as the Cape fig plant belongs to the mulberry family and is a native of tropical Africa and the Cape Islands. Pharmacological studies have validated significant actions of different extracts as antimicrobial, relaxation of gastrointestinal tract, antioxidant and immune-booster agents, thus supporting some of its folkloric uses. This study was done to document the ethnomedicinal uses, phytochemical constituents, as well as the pharmacological activities of the plant Ficus capensis.